Pengaruh Kompetensi, Profesionalisme, Integritas, dan Independensi Terhadap Kualitas Audit Dengan Etika Audit Sebagai Pemoderasi - Dewi Etika Cahya (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to determine the effect competence, professionalism, integrity, and independence on audit quality with audit ethics as a moderating variable at the Public Accounting Firm in Medan City. The sample selection method used is non probability sampling. The total population in this study was 24 public accounting firms with a sample size of 5 public accounting firms consisting of 44 auditors. The data analysis technique used in this research is Moderated Regression Analysis. The test results in this research indicate that together competence, professionalism, integrity, and independence have an effect on audit quality. Partially, competence, professionalism, integrity, and independence affect audit quality. Moderation analysis shows that audit ethics is able to moderate the effect of competence, professionalism, integrity, and independence on audit quality on PAF in Medan City.